The Yin and Yang of Nicotine: Harmful during Development, Beneficial in Adult Patient Populations - Counotte, Danielle S.; Smit, August B.; Spijker, Sabine (Frontiers in Pharmacology, 2012)
Nicotine has remarkably diverse effects on the brain. Being the main active compound in tobacco, nicotine can aversively affect brain development. However, it has the ability to act positively by restoring attentional capabilities in smokers. Here, we focus on nicotine exposure during the prenatal and adolescent developmental periods and specifically, we will review the long-lasting effects of nicotine on attention, both in humans and animal models. We discuss the reciprocal relation of the beneficial effects of nicotine, improving attention in smokers and in patients with neuropsychiatric diseases, such as schizophrenia and attention deficit/hyperactivity disorder, versus nicotine-related attention deficits already caused during adolescence. Given the need for research on the mechanisms of nicotine’s cognitive actions, we discuss some of the recent work performed in animals.